The Role of South Korea’s Public Diplomacy Through Korea Foundation in Indonesia - Zamzami, Fauzi Wahyu (Universitas Muhammadiyah Yogyakarta, 2021)
This study explored and identified South Korea’s public diplomacy through the Korea Foundation in Indonesia. The Korea Foundation is a non-profit public diplomacy organization founded in 1991. The main mission is to promote a better understanding of Korea and establish relations with the international community through various cultural exchange programs. The presence of the Korea Foundation in Indonesia is the answer to the many Indonesian people's interest in Korean culture. The purpose of this study is to analyze the role of South Korea’s public diplomacy through the Korea Foundation in Indonesia. This topic used three main dimensions of Mark Leonard's concept of public diplomacy, namely News Management, Strategic Communication, and Relationship Building, and qualitative methods with data analysis techniques through literature related to the topic. Basically, there is a lot of literature that discussed South Korea’s public diplomacy. However, no one has focused on South Korea’s public diplomacy through the Korea Foundation, especially in Indonesia. The results of this study indicated that the Korea Foundation applied several strategies for South Korea’s public diplomacy through various cultural exchange activities, research, and language learning. The Korea Foundation is also an example that non-profit organizations have a strategic role in South Korea’s public diplomacy which has succeeded in attracting the attention of the Indonesian people and building sustainable relationship.